2022
DOI: 10.1002/jcsm.13105
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of cancer cachexia in patients: Assessment of healthcare providers' knowledge and practice gaps

Abstract: Background Cancer cachexia negatively impacts patient outcomes, quality of life and survival. Identification and management of cancer cachexia remains challenging to healthcare professionals (HCPs). The aim of this assessment was to identify current gaps in HCPs' knowledge and practice for identifying and managing adults with cancer‐related cachexia. Results may guide development of new educational programmes to close identified gaps and improve outcomes of cancer patients. Methods An international assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…They also show that educated healthcare professionals are more likely to be aware of guidelines and to have the confidence to provide patients with nutritional advice [20]. However, education and training in cancer cachexia is reported to be inadequate [21,22 ▪ ,23] despite being recognized for its potential to improve practice [22 ▪ ,24].…”
Section: The Need For Education In Cancer Cachexia: Health Care Profe...mentioning
confidence: 99%
“…They also show that educated healthcare professionals are more likely to be aware of guidelines and to have the confidence to provide patients with nutritional advice [20]. However, education and training in cancer cachexia is reported to be inadequate [21,22 ▪ ,23] despite being recognized for its potential to improve practice [22 ▪ ,24].…”
Section: The Need For Education In Cancer Cachexia: Health Care Profe...mentioning
confidence: 99%
“…In fact, in a questionnaire survey of Japanese healthcare professionals, only 17.4% of those assessed cachexia on their own 18 . Recent international quantitative survey showed that only 29.1% of respondents recognized a key criterion of cancer cachexia as >5% weight loss from baseline 19▪▪ . Many respondents (37.3%) believed that cachexia was inevitable.…”
Section: Clinical Practice In Japan For Patients With Cancer Cachexiamentioning
confidence: 99%
“…The results of this multinational survey of interprofessional oncologic providers were recently published and offer a clinician point of view for the challenges of caring for patients with CC. 8 The results of the survey were sobering, as they revealed the belief by nearly 40% of respondents that cachexia is an inevitable reality for patients with cancer. Nearly 50% of respondents were very or somewhat confident in their ability to provide care for patients with CC despite many respondents reporting no use of a standardized definition of CC at their practice site and that the terms malnutrition and cachexia were often used interchangeably to describe cancer-related weight loss.…”
mentioning
confidence: 99%
“…7 The need for further awareness of CC has been identified for patients and their caregivers, but a recent international mixed-method needs assessment was conducted to focus on the gaps in practices and understanding of CC among healthcare practitioners. 8 The mixed-method approach to this project included the creation of two levels of advisory boards from members of in-country collaborating organizations. The American Society for Parenteral and Enteral Nutrition (ASPEN) was represented by members of the ASPEN Oncology Section and was one of four collaborative organizations who participated in the global project led by the Society on Cachexia and Wasting Disorders (SCWD).…”
mentioning
confidence: 99%
See 1 more Smart Citation